2016
DOI: 10.1002/hed.24408
|View full text |Cite
|
Sign up to set email alerts
|

Transoral laser microsurgery for locally advanced (T3-T4a) supraglottic squamous cell carcinoma: Sixteen years of experience

Abstract: TLM constitutes a true alternative for organ preservation in locally advanced supraglottic carcinomas with good oncologic and functional outcomes. © 2016 Wiley Periodicals, Inc. Head Neck 38: 1050-1057, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 44 publications
2
25
0
Order By: Relevance
“…Accordingly, Hinni et al [32] demonstrated a laryngeal preservation rate of 86% and a 5-year overall and diseasefree survival of 50 and 53%, respectively; Rudert at el [53] confirmed a 5-year overall survival of 47% and Motta of 77% for T3 patients with a laryngeal preservation rate of 93.7% [54]. Vilaseca et al [41] published one of the largest series on 154 patients with T3-T4 supraglottic cancers treated with TLM, by obtaining an OS and DFS rates ranging from 67 to 90%, with a laryngeal preservation percentage up to 85.…”
Section: Discussionmentioning
confidence: 96%
“…Accordingly, Hinni et al [32] demonstrated a laryngeal preservation rate of 86% and a 5-year overall and diseasefree survival of 50 and 53%, respectively; Rudert at el [53] confirmed a 5-year overall survival of 47% and Motta of 77% for T3 patients with a laryngeal preservation rate of 93.7% [54]. Vilaseca et al [41] published one of the largest series on 154 patients with T3-T4 supraglottic cancers treated with TLM, by obtaining an OS and DFS rates ranging from 67 to 90%, with a laryngeal preservation percentage up to 85.…”
Section: Discussionmentioning
confidence: 96%
“…7 Many series have reported the outcomes of TLM in laryngeal cancer, pointing out some of the risks and complications of this type of surgery. [12][13][14][15][16][17][18] With such controversial evidence, it is difficult sometimes to decide between TLM and other therapeutic approaches. 11 For this reason, some authors recommend TLM only in early or selected intermediate cases, 11 whereas others have published large series with good results in locally advanced cases.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] In series with T1 midcord tumors the risk of local relapse is usually under 6%. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] In series with T1 midcord tumors the risk of local relapse is usually under 6%.…”
Section: Discussionmentioning
confidence: 99%
“…There is a high level of consensus on the use of TLAR in T4a LSCC, but the clinical diversity and heterogeneity of T3 laryngeal cancers represent a major challenge to established guidelines [17,27]. Based on the idea of organ preservation, TLM and open/endoscopic partial laryngectomies have been proposed as therapeutic alternatives to radiotherapy or chemoradiotherapy in several publications [28,29]. Canis et al and Peretti and colleagues have reported five-year OS of 64.4% and 63.3% in two studies where TLM was used as the primary approach to T3 glottic and supraglottic LSCC, respectively [30,31].…”
Section: Discussionmentioning
confidence: 99%